The Lagrangian particle trajectory output and the metadata of the Southern Ocean Biogeochemical Divide location for 'Localizing the Southern Ocean Biogeochemical Divide' - Yinghuan Xie; Veronica Tamsitt; Lennart Bach (Zenodo, 2022)
1. Trajectory files The Lagrangian particle trajectory output files from virtual particle release experiments at the surface and 500m depth using Connectivity Modeling System (Paris et al. 2013, https://github.com/beatrixparis/connectivity-modeling-system) run offline in the ACCESS-OM2-01 model (Kiss et al., 2020), a global 0.1° ocean sea-ice model, with a JRA55-do repeat year neutral state atmospheric forcing (Stewart et al., 2020). These trajectory datasets are compressed to two .rar format files for 2 depths, which were outputted from the Connectivity Modeling System v2.0 (CMS) in NetCDF format. Trajectory files include latitude, longitude, depth, interpolated along-track salinity and interpolated along-track temperature for each particle which are outputted every five days in the virtual particle tracking experiment. In addition, these datasets also contain the "exitcode" and release date information of each particle. More information please see in the CMS user guide. Other experiment setup files included in each release directory are "nest_1.nml", "runconf.list" and "ibm.list". These datasets are the original data output by the CMS. Limited by multiple nodes and maximum running time on the supercomputer, the surface release experiment is composed of 5 consecutive sub-experiments, and the 500m release experiment is composed of 3 consecutive sub-experiments. Each sub-experiment contains 48 independent output NetCDF files. 2. SOBD files These two .rar SOBD files are original arrays of the percentage of the upper cell minus the lower cell (i.e., the SOBD percentage) at surface and 500m depth (as presented in Fig.3 in Localizing the Southern Ocean Biogeochemical Divide). We provide original arrays in both .csv and .npz formats. More information can be found in the "Readme.txt" file in each .rar file. Citation of associated paper: Y. Xie, V. Tamsitt, L. T. Bach Localizing the Southern Ocean Biogeochemical Divide. to be submitted to Geophysical Research Letters References: Kiss, A. E., Hogg, A. M., Hannah, N., ...